Eastward radiation of C4 crops from the Hongshan culture core region initiated around 6 ka - Licheng Guo; Qiaowen Zhang; Shiling Yang; Shangfa Xiong; Zihua Tang; Zhe Liu; Jingyi Cui; Linlin Cui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A low-cost solar disinfection platform: hydrogel-encapsulated benzyl frameworks for continuous in situ H2O2-driven water treatment - Wenjuan Zhang; Lizheng Chen; Xiaojuan Zhao; Shiling Zhang; Chongling Cheng; Juan Du; Kaikai Ba; Bo Wang; Tengfeng Xie; Xuefeng Chu; Gang Liu; Dayang Wang (Water Research, 2026)

Spatiotemporal characteristics of surface longwave radiation over China from the situ measured data - Shiling Zhang; Mengqi Liu; Bo Hu (Atmospheric Research, 2026)

Autophagy attenuates the secondary senescence of endometrial stromal cells induced by Bisphenol S - Xuguang Mi; Jianhua Fu; Lei Liu; Lingshan Wang; Shiling Chen; Mengxue Wu; Chunxue Niu; Yan Wang; Lixin Cao; Lin Wang; Ling Deng; Xiaodan Lu; et al. (Chemico-Biological Interactions, 2026)

Cerium-iron symbiotic nanozyme alleviates drought stress in wheat by targeting stomatal regulation and photosynthesis - Keyu Chen; Xiaowei Wang; Tao Yuan; Gehong Su; Chun Wu; Mengmeng Sun; Yanying Wang; Ming Hao; Xue Chen; Shiling Feng; Fuyong Wu; Dengcai Liu; et al. (Bioresource Technology, 2026)

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Enantioselective metabolic mechanism and metabolism pathway of tetraconazole in human liver microsomes: In vitro and in silico study - Shiling Liu; Junqi Zhu; Yu Wang; Wenyu Dai; Ya Zhou; Tengfei Zhang; Xianzhang Yang; Jingjing Wu; Yanmei Liu; Jie Luo; Huihua Tan; Feng Zhao (Environmental Pollution, 2026)

Metamifop-induced human breast cancer cells proliferation: Revealing a proliferation mechanism distinct from 17β-estradiol - Jingjing Wu; Ya Zhou; Yu Wang; Junqi Zhu; Lu Lin; Huihua Tan; Shiling Liu; Yahui Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2026)

Ultrasound-assisted phosphorylation-modified sunflower meal protein: characterization and evaluation as a polyphenol delivery system - Zeliang Qi; Jiaxin Jin; Haojuan Chen; Jinsong He; Yazhi Liu; Haotian Cui; Yi Yang; Shiling Lu; Juan Dong; Qingling Wang (Journal of Food Engineering, 2026)

Promotion of CeO2 in Mn3O4-CeO2 composite towards the catalytic oxidation of Butyl acetate - Fuding Tan; Peng Liu; Yahao Liu; Shiling Yang; Xiaoju Lin; Xiaoliang Liang; Steven L. Suib; Daiqi Ye (Journal of Environmental Sciences, 2026)

Analysis of key factors affecting the production of biogenic amines in Xinjiang air-dried beef - Rong Huang; Yutong Bai; Chengwei Liu; Ying Huang; Jianhao Geng; Shiling Lu; Honghong Yu; Jun Liu (Food Bioscience, 2026)

Enhanced degradation of carbamazepine in water by a chitosan-supported tea polyphenols/nano-zero-valent iron system: Mechanistic insights and toxicological risk assessment - Weiwei Yu; Yuanxin Liu; Jianglin Tan; Yue Liang; Jiang Hu; Qing Tu; Shuo Yang; Ji Li; Sikai Zhao; Yang Liu; Xinyan Li; Yan Luo; et al. (Journal of Cleaner Production, 2025)

Highly efficient degradation of sulfamethoxazole by peroxydisulfate activated with phosphoric acid-modified biochar-supported copper sulfide: Performance, mechanisms, and potential applications - Weiwei Yu; Xiyin Zheng; Xi Chen; Cong Liu; Bolin Li; Lu Lv; Yuanxin Liu; Ji Li; Xinyan Li; Yan Luo; Dan Liu; Shiling Chen (Journal of Environmental Chemical Engineering, 2025)

The xylem anatomical structure, physiological characteristics and aromatic components analyses explain the difference of fungal solution induced agarwood formation in Aquilaria sinensis - Shengjiang Pang; Weiwei Zhao; Guihua Huang; Qingbin Jiang; Zaizhi Zhou; Qingqing Zhang; Zuwei Tian; Pei Zhang; Zhongguo Li; Shuokun Deng; Shiling Liu; Baoguo Yang (Trees, 2025)

Juvenile hormone signaling regulates apoptosis mediated chlorantraniliprole sensitivity in Spodoptera frugiperda (Lepidoptera: Noctuidae) - Jie Luo; Huili Ouyang; Shiling Liu; Haiyan Wu; Faqian Xiong; Taiyi Yang; Honghong Li; Xuesheng Li (Pesticide Biochemistry and Physiology, 2025)

Human umbilical cord mesenchymal stem cell-derived exosomes repair raloxifene-induced damage in endometrial stromal cells via autophagy activation - Shiling Chen; Xiuying Lin; Lei Liu; Jianhua Fu; Xiaodan Lu; Chunxue Niu; Qilai Wang; HaiFeng Wei; Mengxue Wu; Munan Sun; Lixin Cao; Xuguang Mi; et al. (Reproductive Toxicology, 2025)

Acidic-thermal coupled degradation of tylosin by using magnetic sulfonated resins under microwave irradiation - Caitiao Fang; Wei Zhang; Chunmei Wang; Shiling Li; Xiaomin Dou; Jun Liu (Journal of Environmental Sciences, 2025)

Characterization of ultrasound-induced soybean peptide particles (SPPs) and SPP-stabilized Pickering emulsions combined with amino acid sequence analysis - Ping Han; Mou Zhao; Zhouping Wang; Nengmao Chen; Fuguo Liu; Shiling Lu; Juan Dong; Jingtao Sun (Food Hydrocolloids, 2025)

Correcting microplastic pollution and risk assessment in Chinese watersheds - Feng Yu; Weiwei Yu; Yan Zhao; Yue Liang; Jiang Hu; Rongqi Liu; Shiling Chen; Qinwei Chen; Yuanxin Liu; Xiyin Zheng; Xinyan Li (Environmental Pollution, 2025)

Evolving Therapeutic Landscape of Intracerebral Hemorrhage: Emerging Cutting-Edge Advancements in Surgical Robots, Regenerative Medicine, and Neurorehabilitation Techniques - Danyang Chen; Zhixian Zhao; Shenglun Zhang; Shiling Chen; Xuan Wu; Jian Shi; Na Liu; Chao Pan; Yingxin Tang; Cai Meng; Xingwei Zhao; Bo Tao; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the most serious form of stroke and has limited available therapeutic options. As knowledge on ICH rapidly develops, cutting-edge techniques in the fields of surgical robots, regenerative medicine, and neurorehabilitation may revolutionize ICH treatment. However, these new advances still must be translated into clinical practice. In this review, we examined several emerging therapeutic strategies and their major challenges in managing ICH, with a particular focus on innovative therapies involving robot-assisted minimally invasive surgery, stem cell transplantation, in situ neuronal reprogramming, and brain-computer interfaces. Despite the limited expansion of the drug armamentarium for ICH over the past few decades, the judicious selection of more efficacious therapeutic modalities and the exploration of multimodal combination therapies represent opportunities to improve patient prognoses after ICH.

Comprehensive study of flusulfinam in paddy water–sediment microcosms: Enantioselective fate, degradation pathways, and toxicity assessment - Shiling Liu; Xiaoli Li; Siying Qin; Heng Zhang; Tengfei Zhang; Junqi Zhu; Lu Lin; Lei Lian; Fayang Xie; Huihua Tan; Feng Zhao (Journal of Hazardous Materials, 2025)

Basing target enzyme study the enantioselective bioactivity action mechanism of flusulfinam, a novel HPPD inhibitor herbicide - Shiling Liu; Siying Qin; Tengfei Zhang; Heng Zhang; Junqi Zhu; Xiaoli Li; Yuanfu Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2025)

Dual-active-site design of FeNi3 for electrocatalytic nitrate reduction to ammonia - Kaiyu Qu; Xiaojuan Zhu; Leyang Song; Jing Wang; Yushuang Gong; Xiang Liu; Shiling Yuan; Qipeng Lu; Yifu Yu; An-Liang Wang (Chemical Engineering Journal, 2025)

Simultaneous removal of methane and high nitrite from the wastewater by Methylomonas sp. with soluble methane monooxygenase - Yuxuan Sang; Qinqin Hao; Yuechao Zhang; Oumei Wang; Shiling Zheng; Fanghua Liu (Bioresource Technology, 2025)

Gelatin/polyvinyl alcohol films loaded with doubly stabilized clove essential oil chitosomes: Preparation, characterization, and application in packing marinated steaks - Cenchen Ran; Qingqing Li; Mou Zhao; Haotian Cui; Yi Yang; Kui Diao; Yazhi Liu; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2024)

MicroRNA-451 Regulates Angiogenesis in Intracerebral Hemorrhage by Targeting Macrophage Migration Inhibitory Factor - Shuang Bai; Ge Zhang; Shiling Chen; Xuan Wu; Jiarui Li; Jingxuan Wang; Danyang Chen; Xia Liu; Jiahui Wang; Yuanwei Li; Yingxin Tang; Zhouping Tang (Molecular Neurobiology, 2024)
Intracerebral hemorrhage (ICH) is a subtype of stroke with the highest fatality and disability rate. Up to now, commonly used first-line therapies have limited value in improving prognosis. Angiogenesis is essential to neurological recovery after ICH. Recent studies have shown that microRNA-451(miR-451) plays an important role in angiogenesis by regulating the function of vascular endothelial cells. We found miR-451 was significantly decreased in the peripheral blood of ICH patients in the acute stage. Based on the clinical findings, we conducted this study to investigate the potential regulatory effect of miR-451 on angiogenesis after ICH. The expression of miR-451 in ICH mouse model and in a hemin toxicity model of human brain microvascular endothelial cells (hBMECs) was decreased the same as in ICH patients. MiR-451 negatively regulated the proliferation, migration, and tube formation of hBMECs in vitro . MiR-451 negatively regulated the microvessel density in the perihematoma tissue and affected neural functional recovery of ICH mouse model. Knockdown of miR-451 could recovered tight junction and protect the integrity of blood-brain barrier after ICH. Based on bioinformatic programs, macrophage migration inhibitory factor (MIF) was predicted to be the target gene and identified to be regulated by miR-451 inhibiting the protein translation. And p-AKT and p-ERK were verified to be downstream of MIF in angiogenesis. These results all suggest that miR-451 will be a potential target for regulating angiogenesis in ICH.

Unexpected methane oxidation acceleration by two species of bacteria from the rainwater promoting Methylomonas sp. in the soil - Yuxuan Sang; Jia Tang; Oumei Wang; Qinqin Hao; Shiling Zheng; Fanghua Liu (Journal of Environmental Chemical Engineering, 2024)

Comprehensive study of chiral herbicide flusulfinam uptake, translocation, degradation, and subcellular distribution in rice (Oryza sativa L.) - Shiling Liu; Xiaoli Li; Heng Zhang; Siying Qin; Liying Liang; Ying Liao; Junqi Zhu; Huihua Tan; Feng Zhao (Pesticide Biochemistry and Physiology, 2024)

Assessing the structural and foaming property changes in egg yolk proteins due to malondialdehyde: Experimental and molecular docking studies - Jingya Chen; Jiaxin Jin; Yu Liu; Mengbin Zhao; Zeliang Qi; Wenjing Shi; Yangyang Li; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2024)

Extraction and identification of polyphenol from Camellia oleifera leaves using tailor-made deep eutectic solvents based on COSMO-RS design - Shiling Feng; Guanfeng Deng; Huanyao Liu; Haiqiu Shi; Pingjin Li; Xiao Li; Tao Chen; Lijun Zhou; Ming Yuan; Chunbang Ding (Food Chemistry, 2024)

Correction to: Effects of Dl-3‑n‑butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of Dl-3-n-butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Vascular cognitive impairment (VCI) has been one of the major types of cognitive impairment. Blood–brain barrier damage plays an essential part in the pathogenesis of VCI. At present, the treatment of VCI is mainly focused on prevention, with no drug clinically approved for the treatment of VCI. This study aimed to investigate the effects of DL-3-n-butylphthalide (NBP) on VCI rats. A modified bilateral common carotid artery occlusion (mBCCAO) model was applied to mimic VCI. The feasibility of the mBCCAO model was verified by laser Doppler, 13 N-Ammonia-Positron Emission Computed Tomography (PET), and Morris Water Maze. Subsequently, the Morris water maze experiment, Evans blue staining, and western blot of tight junction protein were performed to evaluate the effect of different doses of NBP (40 mg/kg, 80 mg/kg) on the improvement of cognitive impairment and BBB disruption induced by mBCCAO. Immunofluorescence was employed to examine the changes in pericyte coverage in the mBCCAO model and the effect of NBP on pericyte coverage was preliminarily explored. mBCCAO surgery led to obvious cognitive impairment and the decrease of whole cerebral blood flow, among which the blood flow in the cortex, hippocampus and thalamus brain regions decreased more significantly. High-dose NBP (80 mg/kg) improved long-term cognitive function in mBCCAO rats, alleviated Evans blue leakage and reduced the loss of tight junction proteins (ZO-1, Claudin-5) in the early course of the disease, thereby exerting a protective effect on the blood–brain barrier. No significant changes in pericyte coverage were observed after mBCCAO. High-dose NBP improved cognitive function in mBCCAO rats. High-dose NBP protected the integrity of BBB by upregulating TJ protein expression, rather than regulating pericyte coverage ratio. NBP could be a potential drug for the treatment of VCI.

Surgical Robotics for Intracerebral Hemorrhage Treatment: State of the Art and Future Directions - Zhuojin Wu; Danyang Chen; Chao Pan; Ge Zhang; Shiling Chen; Jian Shi; Cai Meng; Xingwei Zhao; Bo Tao; Diansheng Chen; Wenjie Liu; Han Ding; et al. (Annals of Biomedical Engineering, 2023)
Intracerebral hemorrhage (ICH) is a stroke subtype with high mortality and disability, and there are no proven medical treatments that can improve the functional outcome of ICH patients. Robot-assisted neurosurgery is a significant advancement in the development of minimally invasive surgery for ICH. This review encompasses the latest advances and future directions of surgical robots for ICH. First, three robotic systems for neurosurgery applied to ICH are illustrated. Second, the key technologies of robot-assisted surgery for ICH are introduced in aspects of stereotactic technique and navigation, the puncture instrument, and hematoma evacuation. Finally, the limitations of current surgical robots are summarized, and the possible development direction is discussed, which is named “multisensor fusion and intelligent aspiration control of minimally invasive surgical robot for ICH”. It is expected that the new generation of surgical robots for ICH will facilitate quantitative, precise, individualized, standardized treatment strategies for ICH.

Biodegradation characteristics and mechanism of terbuthylazine by the newly isolated Agrobacterium rhizogenes strain AT13 - Yanmei Liu; Wei Liu; Menghao Li; Shiling Liu; Dingjiao Peng; Feng Zhao; Xiaogang Wu; Huihua Tan (Journal of Hazardous Materials, 2023)

Construction of a dynamic model to predict the growth of Staphylococcus aureus and the formation of enterotoxins during Kazak cheese maturation - Huixue Cai; Sijie Pei; Yan Zhang; Rongrong Liu; Shiling Lu; Baokun Li; Juan Dong; Qingling Wang; Xinrong Zhu; Hua Ji (Food Microbiology, 2023)

Microbial degradation of petroleum characteristic pollutants in hypersaline environment, emphasizing n-hexadecane and 2,4 di-tert-butylphenol - Shiling Liu; Wenjiao Yuan; Xiaolin Yang; Chengbin Li; Yishan Ji; Xin Feng; Meitong Li; Yuhong Xie (Environmental Monitoring and Assessment, 2023)

Evaluation of changes in egg yolk lipids during storage based on lipidomics through UPLC-MS/MS - Yu Liu; Xin Guo; Niannian Wang; Shiling Lu; Juan Dong; Zeliang Qi; Junrong Zhou; Qingling Wang (Food Chemistry, 2023)

Respiratory electrogen Geobacter boosts hydrogen production efficiency of fermentative electrotroph Clostridium pasteurianum - Yuechao Zhang; Shiling Zheng; Qinqin Hao; Oumei Wang; Fanghua Liu (Chemical Engineering Journal, 2023)

Changes in Cerebral Blood Flow and Diffusion-Weighted Imaging Lesions After Intracerebral Hemorrhage - Jingfei Yang; Jie Jing; Shiling Chen; Xia Liu; Yingxin Tang; Chao Pan; Zhouping Tang (Translational Stroke Research, 2022)

Fosthiazate exposure induces oxidative stress, nerve damage, and reproductive disorders in nontarget nematodes - Shiling Liu; Qiqi Wu; Yanru Zhong; Zongzhe He; Zhen Wang; Rui Li; Minghua Wang (Environmental Science and Pollution Research, 2022)

Large‐scale synoptic atmospheric moisture circulation patterns associated with variability of daily precipitation over East China - Bingjun Liu; Shiling Chen; Xuezhi Tan (International Journal of Climatology, 2021)
This study identifies the variability of large‐scale atmospheric patterns (LSMPs) and atmospheric moisture circulation patterns associated with the variability of daily precipitation over East China using the self‐organizing maps (SOM) method. The spatiotemporal characteristics of the occurrence and intensity of daily precipitation were linked with the variabilities of LSMPs. Results show that the synoptic moisture transport over East China in both dry season and rainy season can be classified into eight patterns, and the occurrence frequency and primary occurring months of the eight patterns are varied. In the dry season, the wetter pattern (the drier pattern) exhibits a significant decreasing (increasing) trend with a slope of −0.23 (0.63)% year −1 at the confidence level of 0.95 during 1979–2018. The LSMPs corresponding to each atmospheric moisture circulation pattern, including the composite mean values of vertically integrated water vapour transport fields, 500 hPa geopotential height (Z500) anomalies and sea surface temperature anomalies (SSTA) in surrounding oceans, indicate that the primary oceanic moisture source of the dry season is western North Pacific (WNP), while that of the rainy season is WNP and the Indian Ocean. The location and intensity variabilities of subtropical high affect the transport and amount of water vapour along with its western flank to arrive in East China. SSTA has an influential link with the regional circulations and convection activity, and thus plays an important role in affecting water vapour transport.

Inconsistent changes in global precipitation seasonality in seven precipitation datasets - Xuezhi Tan; Yi Wu; Bingjun Liu; Shiling Chen (Climate Dynamics, 2020)

The differentiation of iron-reducing bacterial community and iron-reduction activity between riverine and marine sediments in the Yellow River estuary - Hongxia Zhang; Fanghua Liu; Shiling Zheng; Lei Chen; Xiaoli Zhang; Jun Gong (Marine Life Science & Technology, 2020)

Inter-comparison of spatiotemporal features of precipitation extremes within six daily precipitation products - Shiling Chen; Bingjun Liu; Xuezhi Tan; Yi Wu (Climate Dynamics, 2020)

Characteristics and circulation background of extreme precipitation over East China - Shiling Chen; Bingjun Liu; Xuezhi Tan; Zeqin Huang (Natural Hazards, 2019)

Antioxidant effect of hawk tea extracts on camellia oil oxidation during microwave heating - Zhou Xu; Xu Li; Shiling Feng; Jing Liu; Lijun Zhou; Ruiwu Yang; Chunbang Ding (Journal of Consumer Protection and Food Safety, 2018)

Comparative transcriptomic insights into the mechanisms of electron transfer in Geobacter co-cultures with activated carbon and magnetite - Shiling Zheng; Fanghua Liu; Meng Li; Leilei Xiao; Oumei Wang (Science China Life Sciences, 2018)

Pseudomonas aeruginosa phage PaP1 DNA polymerase is an A-family DNA polymerase demonstrating ssDNA and dsDNA 3′–5′ exonuclease activity - Binyan Liu; Shiling Gu; Nengsong Liang; Mei Xiong; Qizhen Xue; Shuguang Lu; Fuquan Hu; Huidong Zhang (Virus Genes, 2016)